2012
DOI: 10.2147/vhrm.s29284
|View full text |Cite
|
Sign up to set email alerts
|

Erythrocyte sedimentation rate as a marker for coronary heart disease

Abstract: BackgroundPatients with angina pectoris or myocardial infarction frequently present without evidence of cardiac-specific heart enzymes by laboratory analysis or specific pathologic electro-cardiogram findings. The current study analyzed the efficacy of the erythrocyte sedimentation rate as an additional potential indicator for coronary heart disease, the aim being to enable quicker identification of patients with angina pectoris or myocardial infarction so that they can be more rapidly treated.MethodsPatients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
29
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 18 publications
4
29
0
3
Order By: Relevance
“…Prakash et al2 have pointed to conflicting reports in the literature documenting the tendency of patients with periodontitis to develop anemia. Hence, this study was undertaken to assess whether periodontitis can cause an anemic state by evaluating and comparing the red blood cell count and levels of hemoglobin, hematocrit, ESR, serum iron, and serum ferritin between subjects with and without periodontitis, anemia, rheumatoid arthritis, and other hematologic conditions 1. However, this study shows that there is no statistically significant difference between rates of ESR in men and women.…”
Section: Letter To the Editormentioning
confidence: 90%
See 2 more Smart Citations
“…Prakash et al2 have pointed to conflicting reports in the literature documenting the tendency of patients with periodontitis to develop anemia. Hence, this study was undertaken to assess whether periodontitis can cause an anemic state by evaluating and comparing the red blood cell count and levels of hemoglobin, hematocrit, ESR, serum iron, and serum ferritin between subjects with and without periodontitis, anemia, rheumatoid arthritis, and other hematologic conditions 1. However, this study shows that there is no statistically significant difference between rates of ESR in men and women.…”
Section: Letter To the Editormentioning
confidence: 90%
“…The aim of Yayan’s1 study was to utilize the erythrocyte sedimentation rate (ESR) as a rapid guide to identify patients with acute coronary syndrome (ACS) or myocardial infarction. ESR is arguably a nonspecific biomarker which is elevated in almost every condition.…”
Section: Letter To the Editormentioning
confidence: 99%
See 1 more Smart Citation
“…Manchon et al16 (1988) reported the high recurrence of issues (95%) such as infection, malignancy and inflammation in patients with ESR levels >70 mm/h. Yayan17 showed that ESR usually is high in patients with coronary heart disease, and this may be due to the inflammatory etiology of coronary heart disease. Togan et al7 similarly demonstrated that in male patients who had undergone CABG surgery, the elevated preoperative ESR can bring about midterm postoperative adverse events such as morbidity and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Ein Verfahren, das problemlos mit der Ergometrie verbunden werden kann, bislang jedoch in der Kardiologie wenig zur Anwendung gekommen ist, ist die Spiroergometrie. Hier wird neben dem Belastungs-EKG kontinuierlich das Atemvolumen und über in-und exspiratorische Sauerstoffund Kohlendioxidkonzentrationen auch die Sauerstoffaufnahme ( Blutsenkung und CRP sind zwar ebenfalls mit einem erhöhten kardiovaskulären Risiko assoziiert, sind jedoch sehr unspezifisch und auch bei banalen Infekten erhöht [16,17]. Im Fall der TSH-Bestimmung sind die Hypothyreose sowie die Hyperthyresose mit einem erhöhten kardiovaskulären Risiko assoziiert [18,19].…”
Section: Spiroergometrie In Der Tauglichkeitsuntersuchungunclassified